2019
DOI: 10.1364/oe.27.036767
|View full text |Cite
|
Sign up to set email alerts
|

Ptychography with multiple wavelength illumination

Abstract: For performing phase retrieval in the extreme ultraviolet (EUV) regime more efficiently, developing polychromatic ptychography is desirable. As an alternative to the existing ptychographic information multiplexing (PIM) method, we present an another scheme where all monochromatic exit waves are expressed in terms of the amplitude of the transmission function and the thickness function of the object. Our proposed algorithm is a gradient based method and its validity is studied numerically. In addition, the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For each of these 2D projection reconstructions, the complex object transmission function contains both the amplitude and phase shift information. Then with the phase shift information, all the projections were unwrapped, aligned, and reconstructed using the open-sourced MATLAB package [54,55] developed by cSAXS beamline at Paul Scherrer Institute (PSI), [57] to give the final 3D tomograms. The ED (e Å À3 ) was then calculated from the phase tomograms using the relation as described elsewhere.…”
Section: Morphological Analysis and Imaging Techniquesmentioning
confidence: 99%
“…For each of these 2D projection reconstructions, the complex object transmission function contains both the amplitude and phase shift information. Then with the phase shift information, all the projections were unwrapped, aligned, and reconstructed using the open-sourced MATLAB package [54,55] developed by cSAXS beamline at Paul Scherrer Institute (PSI), [57] to give the final 3D tomograms. The ED (e Å À3 ) was then calculated from the phase tomograms using the relation as described elsewhere.…”
Section: Morphological Analysis and Imaging Techniquesmentioning
confidence: 99%
“…(16), we developed and implemented Algorithm 1 as described in the Appendix. To mitigate ambiguity problems of ptychography [27], e.g., the global phase shift, the conjugate reconstruction, and the raster grid pathology, it is assumed that the probe used in the Monte Carlo experiment is known. To shorten the computation time and to improve the convergence, the conjugate-gradient method [40,57] is implemented in Algorithm 1.…”
Section: Monte Carlo Analysismentioning
confidence: 99%
“…During the last two decades, ptychography has been successfully demonstrated with x-ray radiation sources [11,16,17], electron beams [18], and visible light sources [19]. More recently, many extensions of ptychography have been proposed, including Fourier ptychography [20][21][22], spatially partial coherent ptychography [23][24][25], broadband ptychography [26,27], three-dimensional (3D) ptychography [28][29][30], on-the-fly scanning ptychograhy [31,32], and interference probe ptychography [33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mixed states can be deconvolved, and partial decoherence can be compensated for in advanced reconstruction algorithms, such as ptychographic information multiplexing (PIM) [12,16,17]. PIM extended ptychography to allow for simultaneous imaging with multiple wavelength probe illuminations without significant degradation to reconstruction quality as measured by resolution and signal to noise ratio (SNR) [18]. While these recent developments in advanced ptychographic phase retrieval algorithms are promising for plasma imaging applications, they require transverse scanning of the object thus preventing the possibility of imaging transient, non-reproducible objects.…”
Section: Arxiv:200901337v1 [Physicsoptics] 2 Sep 2020mentioning
confidence: 99%